Nucleophile-induced ring contraction in pyrrolo[2,1-c][1,4]benzothiazines: access to pyrrolo[2,1-b][1,3]benzothiazoles - Lystsova, Ekaterina A.; Dmitriev, Maksim V.; Maslivets, Andrey N.; Khramtsova, Ekaterina E. (Beilstein Journal of Organic Chemistry, 2023)
Pyrrolo[2,1-b][1,3]benzothiazoles are an important class of fused sulfur and nitrogen-containing heterocycles intensively studied in medicinal chemistry and pharmacology. In the present paper, a new synthetic approach to pyrrolobenzothiazoles is developed based on 1,4-thiazine ring contraction in 3-aroylpyrrolo[2,1-c][1,4]benzothiazine-1,2,4-triones under the action of nucleophiles. The proposed approach works well with alkanols, benzylamine, and arylamines. The scope and limitations of the developed approach are studied. The synthesized pyrrolobenzothiazole derivatives represent an interest to pharmaceutics, since their close analogs show CENP-E inhibitory activity, interesting for the targeted cancer therapy development.
Keywords: 1,4-benzothiazine; 1,3-benzothiazole; 1H-pyrrole-2,3-diones; nitrogen heterocycle; sulfur heterocycle